2021
DOI: 10.1029/2020jg005994
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Peatland Productivity and Climate Relationships Across the Western South American Altiplano

Abstract: The South American Altiplano is one of the largest semiarid high‐altitude plateaus in the world. Within the Altiplano, peatlands known as “bofedales” are important components of regional hydrology and provide key water resources and ecosystem services to Andean communities. Warming temperatures, changes in hydroclimate, and shifting atmospheric circulation patterns all affect peatland dynamics and hydrology. It is therefore urgent to better understand the relationships between climate variability and the spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 110 publications
(286 reference statements)
1
16
1
Order By: Relevance
“…The response of vegetation to temperature, also observed by other authors (Maggi et al, 2020) is probably associated with a thermic limit to plant growth described by global analyses of montane systems (Körner, 1999;Pauli & Halloy, 2019). Likewise, the increasing trend in SAVI in the last years, also observed in other high mountains (Gaitań et al, 2015;Chavez et al, 2019;Campbell et al, 2021;Anderson et al, 2021), could be a response to the increase in temperatures (in tune with global warming, Xu et al, 2019;Xu et al, 2020) recorded in both lower elevation meteorological stations. Other authors have suggested that increasing vegetation activity in montane systems is related with the occurrence of anomalous rain and snow episodes (Otto et al, 2011;Anderson et al, 2021).…”
Section: Lakessupporting
confidence: 65%
See 2 more Smart Citations
“…The response of vegetation to temperature, also observed by other authors (Maggi et al, 2020) is probably associated with a thermic limit to plant growth described by global analyses of montane systems (Körner, 1999;Pauli & Halloy, 2019). Likewise, the increasing trend in SAVI in the last years, also observed in other high mountains (Gaitań et al, 2015;Chavez et al, 2019;Campbell et al, 2021;Anderson et al, 2021), could be a response to the increase in temperatures (in tune with global warming, Xu et al, 2019;Xu et al, 2020) recorded in both lower elevation meteorological stations. Other authors have suggested that increasing vegetation activity in montane systems is related with the occurrence of anomalous rain and snow episodes (Otto et al, 2011;Anderson et al, 2021).…”
Section: Lakessupporting
confidence: 65%
“…We classified three types of environments that are dominated by different vegetation communities: peatlands, plains, and hillsides. Peatlands (410 ha were classified as peatlands) are known to be temporarily flooded environments with highly green productive vegetation communities (Izquierdo et al, 2015b;Meneses et al, 2020;Anderson et al, 2021), distinguishable from the semiarid matrix. Plains (1099 ha) and hillsides (3736 ha) are dominated by different vegetation communities and their soils have different water retention capacities.…”
Section: Image Processing and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…water provision by the glacier) may influence species composition through resource constraints and habitat complexity (McCain, 2009;Worm & Tittensor, 2018;Zhang et al, 2020). NDVI has been long used as proxy of productivity of Andean wetlands as it is sensitive to the greenness of photosynthetically active biomass (Anderson et al, 2021;Chávez et al, 2019;Moreau et al, 2003). However, these satellite image analyses do not allow quantifying wetland value as direct feeding habitat for waterbirds.…”
Section: Extent and Quality Of Habitatsmentioning
confidence: 99%
“…Remote sensing is a field of applied science that offers interesting benefits to the study and observation of the environment at different temporal and spatial scales, especially for remote places (Johnson, 1990; Vihervaara et al, 2015). These tools are applied to mapping high‐Andean wetlands (Araya‐Lopez et al, 2018; Izquierdo et al, 2015, 2016) and to characterize some specific ecological processes such as hydrological fluctuations (Casagranda et al, 2019; de la Fuente et al, 2021; Garcia & Otto, 2015; Otto et al, 2011), productivity dynamics (Anderson et al, 2021; Casagranda et al, 2019; Chávez et al, 2019) or temporal above‐ground plant biomass dynamics (Moreau et al, 2003). This applicability could be useful to characterize the biogeographic variability of high‐Andean vegas (Izquierdo et al, 2020) allowing us to analyze and monitor them spectrally.…”
Section: Introductionmentioning
confidence: 99%